2019
DOI: 10.20525/ijrbs.v8i4.274
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Organizational Culture on Organizational Citizenship Behavior with Organizational Commitment as a Mediator

Abstract: The contribution of organizational culture to the organization which includes the uniqueness of values, behavior, and psychology is needed by the organization. It also includes trust, experience, ways of thinking, and organizational expectations. Improving employee behavior into organizational citizenship behavior is needed by every organization. To bring OCB to employees, a well-formed commitment is needed. This study uses a quantitative approach to test 3 hypotheses using path analysis to see the role of med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 16 publications
2
18
0
Order By: Relevance
“…Furthermore, a sense of ownership of employees will foster a better commitment for the company which will ensue in less need for strict control. This statement is in accordance with recent research conducted by Arumi, M., Aldrin, N., & Murti, T (2019), found that not only related to organizational effectiveness but also influencing organizational citizenship behavior (OCB) directly, and maximum influence can be seen when commitment mediates organizational culture and OCB. Related to this research, involvement trait by Denison Model can make the company's scheme to support effective performance and the strategy of workers to support a better work environment and directly or indirectly will improve employee performance.…”
Section: Involvementsupporting
confidence: 93%
“…Furthermore, a sense of ownership of employees will foster a better commitment for the company which will ensue in less need for strict control. This statement is in accordance with recent research conducted by Arumi, M., Aldrin, N., & Murti, T (2019), found that not only related to organizational effectiveness but also influencing organizational citizenship behavior (OCB) directly, and maximum influence can be seen when commitment mediates organizational culture and OCB. Related to this research, involvement trait by Denison Model can make the company's scheme to support effective performance and the strategy of workers to support a better work environment and directly or indirectly will improve employee performance.…”
Section: Involvementsupporting
confidence: 93%
“…Every work done requires standards and the ability to measure oneself or subordinates' performance, compare performance with standards under existing provisions, and continuously evaluate the activities' results to determine the need for corrective action in future activities. Employee loyalty to the company is a behavioral factor that can be used to determine and evaluate employees' ability to survive and carry out their duties and responsibilities to the organization (Arumi et al, 2019). Commitment is perceived as a value orientation toward the organization, demonstrating that individuals seriously consider and prioritize their work and the organization.…”
Section: The Influence Of Organizational Culture On Organizational Engagementmentioning
confidence: 99%
“…They are an added value for the company because they tend to show productive and proactive behavior at work. Commitment is a strong desire of employees to give their best and contribute to an organization's success (Arumi et al, 2019). There are two kinds of commitments that can be distinguished, namely effective commitment and continuance commitments (Mayer, 1997).…”
Section: H1: Job Satisfaction Affects Organizational Citizenship Behaviormentioning
confidence: 99%
“…Culture is determined when a group of people lives in the same environment, attitudes, and behavior (Aldrin & Yunanto, 2019). Organizational culture is an organizational system in which there are meanings, values, and beliefs that become a reference for acting and differentiate one organization from another (Arumi et al, 2019). It is a collection of ideologies, philosophies, values, behavior, attitudes, and norms that apply in an organization (El Badawy et al, 2016).…”
Section: H1: Job Satisfaction Affects Organizational Citizenship Behaviormentioning
confidence: 99%